Kelahiran dan Pendidikan Anak: Aspek Penting dalam Tujuan Perkawinan Katolik - Jenny Fransisca Datu; Maria Filisa Sopiah Sani; Marike Amanda Adeltania (Jurnal Teologi Injili dan Pendidikan Agama, 2025)
Marriage in the Catholic Church is seen as a sacrament that binds partners in holy and inseparable love, with the primary goals being the well-being of the couple, the birth of children, and their education. This research aims to examine the important role of child birth and education in the context of Catholic marriage through a literature review approach. Data is taken from official Church documents such as Family Partnership, The Most Important Education, and the Code of Canon Law, as well as other academic literature. The analysis shows that the birth of a child is a real manifestation of love which demands the moral responsibility of the couple to educate the child in the Catholic faith, while the child's education is a means of passing on moral and spiritual values ​​to the next generation. Modern challenges, such as the influence of technology and family dynamics, require an active spiritual life in the family to support children's faith education. This research has implications for strengthening Catholic family values ​​in facing the complexity of the modern world, as well as providing a theological foundation for Catholic couples to carry out their role as primary and first educators in the family.